The hypogean invertebrate fauna of Georgia (Caucasus). Issue 1 (2nd January 2019) - Barjadze, Shalva; Asanidze, Zezva; Gavashelishvili, Alexander; Soto-Adames, Felipe N.
Abstract : Information about the cave invertebrates of Georgia, Caucasus, is summarised, resulting in 43 troglo- and 43 stygobiont taxa reported from 64 caves. Species distribution analyses were conducted for 61 caves harbouring 58 invertebrate taxa, with the majority of caves (39) located in Apkhazeti (north-western Georgia). In 22 caves from central-west Georgia (Samegrelo, Imereti and Racha-Lechkhumi regions of west Georgia) 31 taxa are reported. Composition of cave fauna differed strongly between the caves in Apkhazeti and the central-west of Georgia. Only two taxa of the total 86 were shared, resulting in negligible similarity (Sørensen-Dice coefficient Ss =4.8%). Rarefaction indicated an increase in number of species with additional sampling could increase species richness from 58 to 76 for caves in Apkhazeti and from 31 to 69 for caves in central-west Georgia. These findings suggest that the low invertebrate species richness observed in caves of western Georgia is the result of insufficient sampling. A pairwise approach to analysing species co-occurrence showed ten positive spatial associations in 7 out of 86 cave species, all from Kveda Shakurani and Tsebelda caves. The species co-occurring in the same microhabitat require further study to understand their relationships.